World Perspective in Philosophy, Religion and Culture - ., K.T.K (Journal of Dharma, 1980)
Jee Singh (ed.), World Perspective in Philosophy, Religion and Culture, Patna: Bharati Bhawan, 1968, pp. xxx + 480, Rs. 50.